RANCANG BANGUN SISTEM PRABAYAR PADA PDAM BERBASIS ARDUINO UNO R3 - Rasmana, Susijanto Tri; Susanto, Pauladie (Journal of Control and Network Systems, 2015)
ABSTRACTToday many PDAM are still using water meter reading system manually. Officers come directly to the clients home to record the numbers on the water meter. But in this way the many hurdles that harm customers and the PDAM. The problem that often occurs is when the water meter reading. In this final project will be made a prototype prepaid payment system on PDAM.The system is divided into two. The first is a server, used for prepaid genarate equipped with encryption systems. The second miniature tools. After performing pulse decryption process then water flow sensor do counter calculates the amount of water to come out in accordance with the pulse. When the pulse runs out system will give the command to close the solenoid valve on the faucet. The prepaid system has accuracy rate of 99.9%.Keywords:PDAM, Flow Water Sensor, Solenoid Valve, Pre-Paid System, Arduino Uno R3